DAYA HAMBAT BAKTERI Staphylococcus aureus EKSTRAK DAUN GAHARU (Aquilaria malea L.) SEBAGAI ANTIBAKTERI - Abdul Rahman Wahid; Dzun Haryadi Ittiqo (Jurnal Insan Farmasi Indonesia, 2019)
Aquilaria malea L. are spread naturally in several countries, one of them in Indonesia. This plant has many benefits ranging from stems and leaves. Agarwood leaves contain various antibacterial compounds such as flavonoids, alkaloids, saponins and tannins. Staphylococcus aureus is a facultative anaerobic gram-positive bacterium which is the cause of infection in wounds in the form of abscesses or a collection of pus. The study aims to determine the inhibitory strength of Staphylococcus aureus bacteria extract of aloes leaves as anti-bacterial. This type of research is laboratory experimental through the disc diffusion method. The concentration of agarwood leaves used is 300, 350, 400, and 450 mg/ml and positive control Amoxicillin. Data were analyzed using One Way Annova. The results of this study showed the average inhibition zone of agarwood leaf extract against Staphylococcus aureus bacteria with agarwood leaf extract concentration of 300 mg/ml (15.33 ± 2.51), concentration of 350 mg/ml (16.33±2.25), concentration of 400 mg/ml (20.5± 2.17), concentration of 450 mg/ml (21.17±3.32) and inhibition zone of Amoxicillin (37±0.00). This concluded that agarwood leaf extract had inhibitory potential for the growth of Staphylocccus aureus bacteria. The biggest inhibition power of Staphyloccus aureus growth was 450 mg/ml (21.17 ± 3.32).